Endotracheal Intubation Using a Video Laryngoscope in Patients Expected to Present Difficult Airway Management - Yoo, Miso; Park, Jongcook; Oh, Sanghoon; Yun, Sohui (British Journal of Healthcare and Medical Research, 2025)
When surgery is scheduled under general anesthesia in patients with anticipated difficult airway, anesthesiologists consider various methods for safe anesthesia management. It is highly variable and will depend on several factors including the patient’s current status and vital signs. Algorithms for the management of difficult airways are already known is American Society of Anesthesiology and the Difficult Airway Society. However, even problems that occurred at the same stage may not be solved in the same way depending on the situation. Therefore, it is important to simulate possible situations in advance and to manage patients by preparing various options. In this case series, we report airway management using video laryngoscopy in three patients with respiratory tract masses causing dyspnea.